2017
DOI: 10.1111/pcmr.12589
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and developmental activation of two neuroendocrine systems that regulate light‐mediated skin pigmentation

Abstract: Lower vertebrates use rapid light-regulated changes in skin colour for camouflage (background adaptation) or during circadian variation in irradiance levels. Two neuroendocrine systems, the eye/alpha-melanocyte-stimulating hormone (α-MSH) and the pineal complex/melatonin circuits, regulate the process through their respective dispersion and aggregation of pigment granules (melanosomes) in skin melanophores. During development, Xenopus laevis tadpoles raised on a black background or in the dark perceive less li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 54 publications
6
25
1
Order By: Relevance
“…Rising melatonin levels induce melanosome aggregation and skin whitening at night (dark), a response that is abolished in pinealectomized larvae (Figure b; Bagnara, , ). In X. laevis , the response occurs at developmental times in which melanopsin is already expressed in the eye and the pineal complex (Bertolesi et al., , ; Provencio et al., ; our own unpublished data). The circuits that control changes in skin colour appear segregated even early in development, in that background adaptation occurs independently of the pineal complex, whereas skin pigmentation responses to differences in illumination occur in the absence of the eye (Figure b).…”
Section: Seeing the Light: Melanopsin Expression And The Evolutionarymentioning
confidence: 96%
See 3 more Smart Citations
“…Rising melatonin levels induce melanosome aggregation and skin whitening at night (dark), a response that is abolished in pinealectomized larvae (Figure b; Bagnara, , ). In X. laevis , the response occurs at developmental times in which melanopsin is already expressed in the eye and the pineal complex (Bertolesi et al., , ; Provencio et al., ; our own unpublished data). The circuits that control changes in skin colour appear segregated even early in development, in that background adaptation occurs independently of the pineal complex, whereas skin pigmentation responses to differences in illumination occur in the absence of the eye (Figure b).…”
Section: Seeing the Light: Melanopsin Expression And The Evolutionarymentioning
confidence: 96%
“…In mammals, pupillary constriction (Chen et al, 2011;Gooley, Lu, Fischer, & Saper, 2003) and sleep induction Lupi et al, 2008) also depend on light activation of ipRGCs. It was only melanopsin expression by skin melanophores of LEI organisms that suggested a function in regulating pigmentation (Isoldi et al, 2005;Rollag et al, 2000), until we showed recently that retinal melanopsin in the eye indirectly regulates pigmentation through activation of a neuroendocrine circuit (Bertolesi, Hehr, & Mcfarlane, 2015;Bertolesi, Hehr, Munn, & McFarlane, 2016;Bertolesi, Song, Atkinson-Leadbeater, Yang, & McFarlane, 2017;Bertolesi, Vazhappilly, Hehr, & Mcfarlane, 2016). Indeed, ipRGCs regulate the secretion of melatonin (Lucas, Freedman, Muñoz, Garcia-Fernández, & Foster, 1999;Lupi et al, 2008;Sekaran et al, 2005) and α-MSH (Bertolesi et al, 2015), which modulate skin pigmentation of LEI and LPI organisms (Jenks, van Overbeeke, & McStay, 1977;Slominski, Tobin, Zmijewski, Wortsman, & Paus, 2008).…”
Section: Seeing the Light: Melanopsin Expression And The Evolutionamentioning
confidence: 99%
See 2 more Smart Citations
“…It is commonly observed in the color change of fish, amphibians and reptiles. PCC is mainly regulated by hormones, whose release is responsive to light [ 20 ]. Hormones inducing pigment dispersion in frogs includes alpha-melanocyte-stimulating hormone (α-MSH), adrenocorticotropic hormone (ACTH) and melanin-concentrating hormone (MCH), while those induce pigment aggregation include melatonin and adrenaline [ 1 ].…”
Section: Introductionmentioning
confidence: 99%